Cenário e perspectiva da produção científica sobre competência em informação (coinfo) no Brasil: Estudo da produção no âmbito da ANCIB - Leite, Cecília; Simeão, Elmira Luzia Melo Soares; De Almeida Nunes, Eny Marcelino; Feres, Fabiene Castelo Branco Glória Georges; Feres, Glória Georges [UNESP]; Freire, Isa Maria; Belluzzo, Regina Celia Baptista [UNESP] (My University, 2016)
Search highlight in the field of Information Science in Brazil, the importance of the publications generated by scientific events, specifically the scope of information literacy (Competência em Informação - CoInfo, in Portuguese), analyzing the work and the production of its main scientific society, the Associação Nacional de Pesquisa e Pós-Graduação em Ciência da Informação - ANCIB. Presents the results of research that involved the document corpus published in the editions of the Encontro Nacional de Pesquisa e Pós-Graduação em Ciência da Informação - Enancib, annual scientific agenda ANCIB, watching literature produced by scientific work on CoInfo presented in all Anais of the Enancib in the period 1994-2015, identifying theme insertion in all of its major working groups. The research used exploratory and descriptive approach, involving documentary and historical research. The search was carried out in the event portal ANCIB-Enancib, from the selection of the works related to the theme CoInfo and seven related terms: information literacy, competência informacional, alfabetização informacional, aprendizagem informacional, alfabetização em informação, letramento informacional, user education. For measurement data we used the Bardin technique. The results show that as of 2009 there is an increase in the production of work on CoInfo presented in Enancib, indicating that the spaces commonly used for the application of methodologies are libraries. These results also show that the document corpus dealing with the subject and the growing interest of researchers for it, coupled with the possibilities of seminars involving this theme in focus in recent programming Post-Enancib's, provides a very promising future vision for the studies, research and the effective consolidation of CoInfo in the field of Information Science in Brazil, and its visibility. In conclusion, presents the efforts made by various institutions for the development of CoInfo in Brazil in international impact event.
Scenario and perspectives of scientific literature on information literacy in Brazil: Study of production within the ANCIB
Keywords: ANCIB; CoInfo; Enancib; Information literacy; Information science; Scientific production